Development of Sign Language Application PESAN KULIAH With Material Substance Modification Based on Student Characteristics with Hearing Impaired - Utomo, Utomo; Rapisa, Dewi Ratih; Damastuti, Eviani; Susanti, Dewi Juwita (Journal of ICSAR, 2023)
Lack of mastery of receptive and expressive language in students with hearing impairments affects the ability to compose scientific papers. Assistive technology for writing scientific papers can support students with hearing impairments in completing scientific paper assignments at various semester levels. This research aims to develop assistive technology that can make it easier for students with hearing impairments to participate in learning in tertiary institutions to create accessible learning for students with hearing impairments. Sign language application “PESAN KULIAH” (Guidelines for Writing Scientific Papers) is made by adjusting the characteristics of hearing impairments to make it easier to understand how to write various kinds of scientific papers. The method used in this research is R and D with ADDIE type. The results of the study show that the “PESAN KULIAH” application which contains explanation features about the types of scientific papers, writing systematics, and examples of scientific papers and is equipped with sign language videos by Sign Language Interpreters is proven to support the understanding of students with hearing impairments in understanding writing procedures and terms. contained in the preparation of papers, scientific reports, scientific articles, and theses.